Diaqua-μ3-oxido-hexakis(μ2-trichloroacetato-κ2 O:O′)(trichloroacetato-κO)trichromium(III) acetonitrile trisolvate - Soume, B.B. Mougang D.; Yahya, Rosiyah; Gan, Seng Neon; Ng, Seik Weng (International Union of Crystallography, 2008)
In the crystal structure of the title compound, [Cr3(C2Cl3O2)7O(H2O)2]·3CH3CN, the trinuclear [Cr3O(H2O)2(Cl3CCO2)7] molecule has an oxide O atom that is connected to one monodentate trichloroacetate-coordinated and two water-coordinated CrIII atoms, the three metal atoms forming the points of an equilateral triangle. Each of the six remaining carboxylate groups bridges a Cr–O–Cr fragment. The cluster interacts with the three solvent molecules through water–acetonitrile O—H⋯N hydrogen bonds. Adjacent clusters are linked by a water–carboxylate O—H⋯O hydrogen bond to give a helical chain. One of the CCl3 groups was found to be disordered over two positions, with the major component having a site-occupancy factor of 0.64 (1).